Strategies for Evading the Charge of Genetic Fallacy within the Framework of Vindicatory Genealogy - Pijas, Paweł (Roczniki Filozoficzne, 2024)
The genetic fallacy is an informal error in reasoning (fallacy) involving confusion between the context of discovery and the context of justification, and the assumption that descriptive premises about the genesis of a given claim have normative significance, determine its logical value, or can be used to justify or refute it. The genetic fallacy thus constitutes a fundamental and perhaps “fatal” objection to philosophical methods that, while focusing on the study of the genesis of beliefs, do not at the same time abandon their normative ambitions. This article aims to present possible strategies of defense against this charge, strategies developed in recent Anglo-Saxon (post) analytic philosophy within the framework of reflection on a relatively new form of such method, which is the so-called vindicatory genealogy (used and analyzed in the works of E. Craig, B. Williams, M. Fricker, M. Queloz, among others). The article consists of three parts. Part one serves to present the method of vindicatory genealogy. In part two, I discuss the issue of genetic fallacy. In the third part, I analyze three strategies for evading the genetic fallacy, formulated in the context of vindicatory genealogy: 1) the normative modesty strategy, 2) the logical strategy, and 3) the functionalist-pragmatic strategy. As a conclusion, I argue that the charge of genetic fallacy need not effectively undermine the normative ambitions of vindicatory genealogy.